2015
DOI: 10.3923/ja.2015.175.179
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance and Genetic Variability among Common Bean Genotypes in Savanna/Pantanal Ecotone

Abstract: A B S T R A C TIn order to evaluate the agronomic performance and estimate the genetic variability of 24 common bean genotypes grown in the Savanna-Pantanal ecotone and see, which characters can be used for selection of superior genotypes. Treatments consisted of 24 common bean genotypes (CNFC Requinte, BRS Pontal, BRS 9435 Cometa e BRS Estilo). The following traits were evaluated: Early flowering, early maturity, height of the first pod, number of pods per plant, number of grains per pod, weight of 100 grains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Except for the characteristics Height of insertion of the first pod, total number of pods per plant, average number of seeds per plant and average grain production, which reached CV of 31.66, 26.23, 27.16 and 32.27%, these higher CV results for these characters in bean culture are expected, since characters linked to production and controlled by several genes tend to be influenced by the environment. High CV values in the bean culture for characters linked to production have been previously reported by Baldissera et al (2014), Rocha et al (2014), Gerrano et al (2015) and Correa et al (2015).…”
Section: Resultssupporting
confidence: 63%
“…Except for the characteristics Height of insertion of the first pod, total number of pods per plant, average number of seeds per plant and average grain production, which reached CV of 31.66, 26.23, 27.16 and 32.27%, these higher CV results for these characters in bean culture are expected, since characters linked to production and controlled by several genes tend to be influenced by the environment. High CV values in the bean culture for characters linked to production have been previously reported by Baldissera et al (2014), Rocha et al (2014), Gerrano et al (2015) and Correa et al (2015).…”
Section: Resultssupporting
confidence: 63%
“…In 2014-2015 in the State of Mato Grosso do Sul, an area of 17,100 ha produced 27,600 tons of grain, with an average yield of 1814 kg/ha (CONAB, 2015). However, in the CerradoPantanal ecotone, little information has been obtained on cultivar performance (Santos et al, 2011;Correa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This region has unique climatic attributes owing to its location in the transition zone between two national biomes: Cerrado and Pantanal . The agronomic performance of common bean genotypes in this region has been assessed by Corrêa et al (2015) and their results demonstrated that it is possible to exceed the current national average. However, studies are needed to investigate the temporal integration between genotypes x years, to evaluate the performance of genotypes over time.…”
Section: Introductionmentioning
confidence: 99%